EVALUATING EFFICACY AND SAFETY OF DUAL ANTIPLATELET TICAGRELOR VERSUS CLOPIDOGREL IN ACUTE ISCHEMIC STROKE AND TIA: A SYSTEMATIC REVIEW - Uyuwn, Muhammad Zilal; Khatulistiwa, Bunga; Fahmi, Wahyuda Nuzul; Prakasa, Indra Putra (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Dual antiplatelet therapy (DAPT) is used to improve outcomes and reduce recurrent stroke in patients with acute ischemic stroke and transient ischemic attack (TIA). Ticagrelor, a reversible P2Y12 receptor antagonist, provides consistent platelet inhibition by preventing platelet aggregation and glycoprotein IIb/IIIa activation. This review compares aspirin combined with ticagrelor versus clopidogrel for efficacy and safety within 90 days of onset. Objective: To systematically evaluate and compare the efficacy and safety of ticagrelor-based versus clopidogrel-based DAPT, each administered alongside aspirin, for early secondary stroke prevention in adult patients presenting with acute ischemic stroke or TIA, with treatment initiated within 24 hours of the index event. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed was searched for randomized controlled trials published between 2020 and June 2025. Risk of bias was assessed using the ROBIS tool. Extracted data included baseline characteristics, recurrent ischemic stroke, and moderate-to-severe bleeding within 90 days. Four eligible studies involving adults aged ≥18 years treated within 24 hours of onset were included. Ticagrelor was administered as a 180-mg loading dose followed by 90 mg twice daily, while clopidogrel was given as a 300-mg loading dose followed by 75 mg once daily. Results: Ticagrelor-based DAPT demonstrated lower rates of recurrent stroke relative to clopidogrel-based therapy. Between-group comparisons revealed no meaningful differences in moderate-to-severe bleeding events or haemorrhagic complications. Conclusion: Ticagrelor demonstrates greater efficacy in reducing recurrent stroke rates compared with clopidogrel, supporting a broader therapeutic option for managing acute ischemic stroke and TIA.